2008
DOI: 10.1016/j.molcel.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Activation and Transformation by NUP214-ABL1 Is Dependent on the Context of the Nuclear Pore

Abstract: Genetic alterations causing constitutive tyrosine kinase activation are observed in a broad spectrum of cancers. Thus far, these mutant kinases have been localized to the plasma membrane or cytoplasm, where they engage proliferation and survival pathways. We report that the NUP214-ABL1 fusion is unique among these because of its requisite localization to the nuclear pore complex for its transforming potential. We show that NUP214-ABL1 displays attenuated transforming capacity as compared to BCR-ABL1 and that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 40 publications
2
76
0
Order By: Relevance
“…4,33,34 Whereas phosphorylation of Tyr-412 is required to stabilize the activation loop in an open conformation and is associated with high catalytic output, phosphorylation on Tyr-245 appears to stabilize an active kinase conformation by interfering with the autoinhibitory binding of the SH3 domain to the SH2-kinase domain linker. As previously published, although Tyr-245 is 24 also data not shown). These results indicated that both NUP214-ABL1 and BCR-ABL1 are constitutively active tyrosine kinases, but the differences in phosphorylation pattern argue that NUP214-ABL1 is a weaker kinase than BCR-ABL1.…”
Section: Nup214-abl1 and Bcr-abl1 Differ An Order Of Magnitude In Thesupporting
confidence: 85%
See 4 more Smart Citations
“…4,33,34 Whereas phosphorylation of Tyr-412 is required to stabilize the activation loop in an open conformation and is associated with high catalytic output, phosphorylation on Tyr-245 appears to stabilize an active kinase conformation by interfering with the autoinhibitory binding of the SH3 domain to the SH2-kinase domain linker. As previously published, although Tyr-245 is 24 also data not shown). These results indicated that both NUP214-ABL1 and BCR-ABL1 are constitutively active tyrosine kinases, but the differences in phosphorylation pattern argue that NUP214-ABL1 is a weaker kinase than BCR-ABL1.…”
Section: Nup214-abl1 and Bcr-abl1 Differ An Order Of Magnitude In Thesupporting
confidence: 85%
“…24,27 Finally, NUP214-ABL1 has attenuated transforming capacity as compared with BCR-ABL1 and preferentially transforms T cells, which is in agreement with its unique occurrence in T-cell ALL. 24 On the basis of these observations, we have performed a thorough comparison of NUP214-ABL1 and BCR-ABL1 to highlight the unique biochemical properties of NUP214-ABL1 and to gain mechanistic insight in the different disease phenotypes caused by these two oncoproteins. Besides absent activation loop phosphorylation, we show that NUP214-ABL1 displays much lower general tyrosine autophosphorylation, higher Michaelis-Menten constant (K M ) and lower relative maximum velocity (V max ) values than BCR-ABL1.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations